Community Based Tourism (CBT) sebagai Model Pengembangan Desa Wisata Adat Desa Ngadas, Kecamatan Poncokusumo Kabupaten Malang - Bambang Dwi Prasetyo; Nufian Susanti Febriani; Wayan Weda Asmara Dewi (Jurnal Ilmu Komunikasi, 2024)
Tourism is one of the important activities that helps aspects of community economic development. Tourism development policies must be supported by all parties so that they can run optimally. The existence of tourism development is able to become an economic driver with the emergence of new jobs for the community, besides that the development of tourism can also prevent environmental damage and loss of local culture, so that later it is hoped that the community will become more aware of tourism activities. Community involvement in tourism development is known as Community Based Tourism (CBT). The success of developing a tourist village itself is largely determined by the potential for tourism attraction that must be owned by the village, one of which is the development of indigenous people-based tourism. This research was conducted using qualitative research through in-depth interviews. The stages in this study include three stages, namely: the pre-research stage to identify problems, objectives and research flow through literature study, then carry out the observation and interview stages to identify challenges and support for the Traditional Tourism Village model, Ngadas Village, Malang Regency, and finally is the final stage where the researcher will map and formulate the design of a tourist village model. The results of the study are that Empowerment of the Ngadas tourism village involves Community Based Tourism (CBT), namely Tourism Awareness Groups (Pokdarwis) and Bumdes of Ngadas Village through the village's local potential which is staged to become an attractive treat for tourists to come visit.